The Effect of Hypertension on Tooth Extraction Patiens - Oksiarti Dwi Pamungkas Sudiman; Eka Arwidya Purbaningrum; Santo Petrus Junjung; Gipta Galih Widodo (International Forum of Researchers and Lecturers, 2026)
Hypertension is a prevalent systemic condition that may significantly influence the safety of dental procedures, including tooth extraction. Elevated and uncontrolled blood pressure increases the risk of intraoperative and postoperative complications, such as excessive bleeding, hypertensive crisis, and cardiovascular events. This study aims to evaluate the impact of hypertension on tooth extraction and to outline appropriate management strategies for affected patients. A literature review approach was employed, analyzing relevant scientific sources on hypertension and dental care. Evidence indicates that procedural stress, anxiety, and pain can induce acute elevations in blood pressure. Furthermore, the use of local anesthetics containing vasoconstrictors requires careful consideration due to potential hemodynamic effects. In conclusion, hypertension is a critical factor in dental treatment planning. Comprehensive preoperative assessment, careful intraoperative monitoring, and appropriate postoperative management are essential to minimize complications and ensure patient safety.